Power-Law Scaling in the Brain Surface Electric Potential - Miller, Kai J. (Public Library of Science, 2009)
Recent studies have identified broadband phenomena in the electric potentials produced by the brain. We report the finding of power-law scaling in these signals using subdural electrocorticographic recordings from the surface of human cortex. The power spectral density (PSD) of the electric potential has the power-law form [Image: see text] from 80 to 500 Hz. This scaling index, [Image: see text], is conserved across subjects, area in the cortex, and local neural activity levels. The shape of the PSD does not change with increases in local cortical activity, but the amplitude, [Image: see text], increases. We observe a “knee” in the spectra at [Image: see text], implying the existence of a characteristic time scale [Image: see text]. Below [Image: see text], we explore two-power-law forms of the PSD, and demonstrate that there are activity-related fluctuations in the amplitude of a power-law process lying beneath the [Image: see text] rhythms. Finally, we illustrate through simulation how, small-scale, simplified neuronal models could lead to these power-law observations. This suggests a new paradigm of non-oscillatory “asynchronous,” scale-free, changes in cortical potentials, corresponding to changes in mean population-averaged firing rate, to complement the prevalent “synchronous” rhythm-based paradigm.